Simulated trawling: Exhaustive swimming followed by extreme crowding as contributing reasons to variable fillet quality in trawl-caught Atlantic cod (Gadus morhua) - Svalheim, Ragnhild Aven; Aas-Hansen, Øyvind; Heia, Karsten; Drangsholt-Karlsson, Anders; Olsen, Stein Harris; Johnsen, Helge K. (2018)
Preprint version available at https://doi.org/10.1101/372581 . Trawl-caught Atlantic cod ( Gadus morhua ) often yield high variable fillet quality potentially related to capture stress. To investigate mechanisms involved in causing variable quality, commercial-sized (size 3.5±0.9 kg) Atlantic cod were swum to exhaustion in a large swim tunnel and exposed to extreme crowding (736±50 kg m3) for 0, 1 or 3 hours in an experimental cod-end. Further, fish were recuperated for 0, 3 or 6 hours in a net pen prior to slaughter to assess the possibility to quickly reverse the reduced quality. We found that exhaustive swimming and crowding were associated with increased metabolic stress, as indicated by increased plasma cortisol, blood lactate and blood haematocrit levels, and a reduced quality of the fillets in terms of increased visual redness and a drop in muscle pH. The observed negative effects of exhaustive swimming and crowding were only to a small degree reversed within 6 hours of recuperation. The results from this study suggest that exhaustive swimming followed by extreme crowding is a likely significant contributor to the variable fillet quality seen in trawl-caught Atlantic cod, and that recuperation for more than six hours may be required to reverse these effects.